The Role of Interpersonal Relationships in Adolescents' Suicidal Behavior: A Qualitative Analysis of Semi-Structured Interviews - N.A. Polskaya; D.K. Yakubovskaya; D.A. Sharova; A.Ya. Basova (Клиническая и специальная психология, 2024)
This article presents the results of a qualitative analysis based on semi-structured interviews conducted with adolescents (n=13, aged 13–17), who were admitted to an inpatient psychiatric facility after attempted suicide. Content analysis yielded groups of words describing the circumstances of the suicide attempt based on semantic proximity. The following groups emerged (ordered by descending frequency of use): words describing one's psychological state, descriptions of family and relatives, words related to studies, school or college, and descriptions of relationships with peers. Within the framework of the thematic analysis, two superordinate themes and nine subthemes were identified, revealing the subjective experience of the suicide attempt. The first superordinate theme, psychological distress, includes the subthemes of “negative thoughts and emotions”, “mental pain” and “fear of surviving”. The second superordinate theme, interpersonal vulnerability, includes the subthemes of “feeling misunderstood by loved ones”, “conflicts”, “loneliness”, “experiencing the loss of important relationships”, “self-destructive way of communicating problems”, “the excessive importance of emotional relationships with peers” and “sensitivity”. These findings suggest that interpersonal relationships may play a significant role in adolescents’ suicide attempts, including both family relationships (primarily relationships with mothers) and relationships with peers; moreover, the state of psychological distress is described by adolescents in direct connection with dissatisfaction with interpersonal relationships (conflicts, rejection, neglect). Thus, interpersonal vulnerability, along with psychological distress, is one of the key characteristics of adolescent suicides.